Requirement Model For Web-Based SUKSIS Trainee Information System - Hapini, Awang (2008)
The Royal Malaysian Police or Polis Diraja Malaysia (PDRM) is a main branch of security forces in Malaysia. Kor Sukarelawan Siswa Polis (SUKSIS) is one of the sub-forces in PDRM that was specially established for university's student. As the numbers of SUKSIS trainees grows year by year, paper based record management is not relevant anymore to be implemented. Thus, this study which is to design requirement model for Web-based SUKSIS Trainee Information System have most contributed to solve the problem. The Unified Modeling Language (UML) with Web Application Extension(WEA) has been utilized to design the architecture of the Web-based SUKSIS Trainee Information System. The Web-based SUKSIS Trainee Information System is being designed as web-based to enable user access it from everywhere and at anytime. The methodology that used in this project is Rapid Application Development (RAD). The users of Web-based SUKSIS Trainee Information System will be SUKSIS management staff, coordinator and trainees. Thus, the requirement model is very important in order to ensure that the Web-based SUKSIS Trainee Information System meet the user's need and can be delivered within expected time and budgets. However, this study only focuses on capturing the functional requirements. This study was concluded by discussing the findings as well as constraints and limitations arising during the course of producing the model, and the recommendation for future study in this domain.